Internet-based self-help using automatic messages and support on demand for generalized anxiety disorder: an open pilot study. Issue 1 (1st January 2020) - Dahlin, Mats; Carlbring, Per; Håkansson, Andreas; Andersson, Gerhard
Abstract: Generalized anxiety disorder (GAD) is a disabling and often chronic condition. Internet-based treatments for GAD have been shown to be effective, but many studies include weekly contact with a therapist with the aim to increase adherence and clinical outcomes. The current study evaluated a less therapist-intensive alternative: support on demand and automatic messages. Thirty-three participants with GAD went through a self-help program targeting excessive worry. Treatment lasted 9 weeks and consisted of seven modules. Participants received short messages with reminders and encouragement. Therapist support was given when asked for. The intervention led to significant and large within-group effects on the primary outcome, Penn State Worry Questionnaire (PSWQ; Cohen's d  = 1.17), as well as on secondary outcomes such as Generalized Anxiety Disorder Questionnaire-IV (GAD-Q-IV; Cohen's d  = 2.71) and Patient Health Questionaire-9 (PHQ-9; Cohen's d  = 1.05). The exception was a small effect on quality of life ( d = −0.34). Twenty-four (74.9%) were satisfied with the treatment and one dropped out. Therapist support was used by 65.6%. Limitations include lack of control condition and a small sample. While preliminary, the findings suggest that self-guided internet interventions can work and be acceptable when automated messages and support on demand is provided.